2021
DOI: 10.3390/ijerph18063269
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Anxiety and Depression among a Cohort of Health Sciences Undergraduate Students: The Prevalence and Risk Factors

Abstract: Stress, anxiety, and depression (SAD) have a negative impact on the learning and academic performance of university students. Hence, this study aimed to determine the prevalence, as well as the risk factors associated with SAD among a cohort of students pursuing undergraduate degree courses in health sciences. This is part of the strategy in building a healthy nation. A questionnaire containing socio-demographic factors and the short version of Depression, Anxiety, and Stress Scale-21 (DASS-21) was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 63 publications
(34 reference statements)
8
64
1
18
Order By: Relevance
“…A total of 21 items including three subscales: depression, anxiety, and stress. The DASS-21 was widely used in the screening of psychological conditions of the general population or clinical patients ( Vignola and Tucci, 2014 ; Yohannes et al, 2019 ; Kuswanto et al, 2020 ; Fauzi et al, 2021 ). Each item used a four-point scoring from “0” (did not apply to me at all) to “3” (applied to me very much or most of the time).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 21 items including three subscales: depression, anxiety, and stress. The DASS-21 was widely used in the screening of psychological conditions of the general population or clinical patients ( Vignola and Tucci, 2014 ; Yohannes et al, 2019 ; Kuswanto et al, 2020 ; Fauzi et al, 2021 ). Each item used a four-point scoring from “0” (did not apply to me at all) to “3” (applied to me very much or most of the time).…”
Section: Methodsmentioning
confidence: 99%
“… Setiawati et al, 2021 , Soh et al, 2020 , Sujadi et al, 2021 , Sun et al, 2021 , Sunjaya et al, 2021 , Tee et al, 2020 , Tee et al, 2020 , Vigo et al, 2021 , Wang et al, 2021 , Chew et al, 2020 , WHO 2020 , Wong et al, 2020 , Woon et al, 2020 , Chew et al, 2020 , Yadav et al, 2021 , Ye et al, 2020 , Chow et al, 2021 , Dai et al, 2020 , Dong and Zheng, 2020 , Ettman et al, 2020 , Fauzi et al, 2021 , Cénat et al, 2020 , Hsieh et al, 2021 , Huang and Zhao, 2021 , Kannampallil et al, 2020 , Khan et al, 2020 , Khan et al, 2021 , Lai et al, 2020 , Lee et al, 2020 , Li et al, 2021 , Li et al, 2021 , Liao et al, 2021 , Lim et al, 2020 , Liu et al, 2021 , Liu et al, 2021 , Chen et al, 2021 , Liu et al, 2021 , Mohd Noor et al, 2021 , NICE 2009 , Chen et al, 2021 , Pak et al, 2020 , Person et al, 2004 , Chen et al, 2021 , Pierce et al, 2020 , Pramukti et al, 2020 , Rahman, 2021 , Roslan et al, 2021 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…In addition to that, normal dopamine release helps the Met/Met carrier to perform better in cognitive tasks under non-stressful conditions [21]. In a related study in which a subset of the subjects comprised of the subjects from our study, it was found that 75.5% of the female subjects experienced normal and mild stress [22]. Furthermore, students bearing the Met allele need a good educational environment to develop full potential for superior cognitive skills which could eventually affect their academic achievement [18].…”
Section: Resultsmentioning
confidence: 72%